Association Between Gender, Coronary Artery Dominance and Severity of Coronary Artery Stenosis on Computed Tomography Angiography - Yohanes Chandra Kurniawan; Rusli Muljadi; Koesbandono; Antonia Anna Lukito; Nata Pratama Hardjo Lugito; Mira Yuniarti (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Coronary artery disease (CAD) is one of the leading causes of death worldwide. Several preliminary studies suggest that certain dominance patterns may be associated with the distribution and severity of stenosis, influencing the risk of cardiac complications and interventional strategies. However, the relationship of gender specific between coronary artery dominance patterns and the severity of stenosis remains poorly understood. This study designed to evaluate the relationship between gender specific, coronary artery dominance, and severity of coronary artery stenosis, number of stenosis vessels, stenosis location, and calcium score on CCTA examination. Methods: A retrospective cross-sectional study with consecutive non-probability sampling was conducted over a one-year period with 1115 patients who underwent CCTA were analysed using the Chi-square test, Fisher’s exact test, and T-test according to the type of data. Result: The result showed a strong association was found between non-right dominant coronary artery (non-RDCA) in females and significant coronary stenosis (p=0.009), with the most strongly associated location being the LCX (p=0.017). Conclusions: These findings suggest the presence of gender- and dominance-specific patterns in coronary artery disease (CAD), warranting further investigation using prospective study designs and larger sample sizes.